Contributions of new technologies to the teaching of English pronunciation - lvalue lvalue (Universitat Jaume I. Department of English Studies, 2018)
Author/s Yolanda Joy Calvo Benzies University of the Balearic Islands, Spain   ABSTRACT One of the most significant changes in language classrooms over recent decades has been the introduction of ICTs. Despite a broad range of previous research in the field, little work has been done to date on assessing the benefits of teaching pronunciation through ICTs, something surprising in view of the large number of existing programs and other materials specifically designed to improve learners' pronunciation. This paper is intended to contribute to the field in that it will provide an overview of the materials currently available for teaching pronunciation through the use of ICTs, as well as an empirical preliminary study on ESP students' first contact with using ICTs for learning pronunciation. Results indicate that these students enjoyed using these technological tools and would like to use them again to practise their pronunciation.